Review of Community Learning Activity Center Service Quality - Wiharjo, Suyadi Murdi; Wulandari, Dian (Journal of Psychology and Sustainable Education, 2024)
The Community Learning Activity Center (PKBM) functions to provide educational services to every member of the community. The aim of this research is to describe a review of the quality of PKBM services. This research uses qualitative methods with a descriptive approach and literature study. Data analysis uses a content approach. The research results show that there are two supporting factors in the service quality improvement strategy: internal and external. The research results have also identified inhibiting factors in service quality improvement strategies: internal and external factors. PKBM and related stakeholders need to respond to the results of this research by paying attention to internal and external factors that support and hinder the quality of PKBM services.